Respuesta :
standard form is ax+by=c
where a and b are normally integers and a is positive
first, get rid of that nasty fraction
times both sides by 3
3y+12=2(x+7)
distribute
3y+12=2x+14
minus 2x from both sides
-2x+3y+12=14
minus 12 from both sides
-2x+3y=2
times both sides by -1
2x-3y=-2
where a and b are normally integers and a is positive
first, get rid of that nasty fraction
times both sides by 3
3y+12=2(x+7)
distribute
3y+12=2x+14
minus 2x from both sides
-2x+3y+12=14
minus 12 from both sides
-2x+3y=2
times both sides by -1
2x-3y=-2